Protein Encapsulation: A Nanocarrier Approach to the Fluorescence Imaging of an Enzyme-Based Biomarker - Jia, Zhiyuan; Han, Hai-Hao; Sedgwick, Adam C.; Williams, George T.; Gwynne, Lauren; Brewster, James T.; Bull, Steven D.; Jenkins, A. Toby A.; He, Xiao-Peng; Schönherr, Holger; Sessler, Jonathan L.; James, Tony D. (Frontiers in Chemistry, 2020)
We report a new pentafluoropropanamido rhodamine fluorescent probe (ACS-HNE) that facilitates the selective detection of neutrophil elastase (NE). ACS-HNE displayed high sensitivity, with a low limit of detection (< 5.3 nM), and excellent selectivity towards elastase over other relevant biological analytes and enzymes. The comparatively poor solubility and cell permeability of ACS-HNE was improved by creating a ACS-HNE-albumin complex; this approach allowed for improvements in the in situ visualisation of elastase activity in RAW264.7 cells relative to ACS-HNE alone. As such the present study serves to demonstrate a simple strategy that may be used to overcome cell impermeability and solubility limitations, and to prepare probes suitable for the cellular imaging of enzymatic activity in vitro.